High-Value Experience, High-Value Market Segments, and Sustainability Principles in Quality Tourism: Case Studies on Community-based Tourism Destinations in Indonesia - Ike Janita Dewi; Sri Ismulyati; Ginta Ginting (Ilomata International Journal of Management, 2022)
Quality tourism which has been recently proposed as the tourism development paradigm is still poorly defined. This paper attempts to explore the literature on this subject. Having visited quality tourism in tourism, sustainable tourism, and marketing-related literature, we propose that it pertains to three aspects 1) quality, high-value, and satisfying tourism products and services, 2) consumers who will ‘happily’ pay more to enjoy the high-value experience, and 3) aspect of ethics, transparency, and respect towards human, nature, and culture. Further, using the three aspects of quality tourism as a framework, case studies are presented to (1) analyze the adoption of the quality tourism paradigm at community-based tourism destinations in Yogyakarta and, (2) propose recommendations to transform these destinations to become quality tourism destinations. The case studies on three tourism villages as community-based tourism destinations that some aspects to be enhanced include the development of High-Value Experience as Represented by the Price of Tourism Products/Packages, marketing strategies to target High-value Market Segments, and further adoption of sustainable tourism development practices.